2023
DOI: 10.3171/2022.4.spine22182
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for cervical kyphotic deformity following laminoplasty: a systematic review and meta-analysis

Abstract: OBJECTIVE Laminoplasty is a common treatment for cervical spondylotic myelopathy (CSM) and for ossification of the posterior longitudinal ligament (OPLL). However, approximately 21% of patients undergoing laminoplasty develop cervical kyphotic deformity (KD). Because of the high prevalence rate of KD, several studies have sought to identify predictors for this complication, but the findings remain highly inconsistent. Therefore, the authors performed a systematic review and meta-analysis to establish reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a large metaanalysis conducted by Azimi et al, patients with cervical pathology had increased T1 slope (healthy 24.5 • , symptomatic 25.7 • ) and cSVA (healthy 18.7 • , symptomatic 22.7 • ) relative to an asymptomatic control group [18]. Additionally, an elevated T1 slope and cSVA predict postoperative kyphotic deformity as the center of the head mass is anteriorly pushed [19,20]. A similar metric, the center gravity of the head to C7 SVA (CGH-C7SVA), is also associated with increased risk of postoperative kyphotic failure following laminoplasty [20].…”
Section: Sagittal Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large metaanalysis conducted by Azimi et al, patients with cervical pathology had increased T1 slope (healthy 24.5 • , symptomatic 25.7 • ) and cSVA (healthy 18.7 • , symptomatic 22.7 • ) relative to an asymptomatic control group [18]. Additionally, an elevated T1 slope and cSVA predict postoperative kyphotic deformity as the center of the head mass is anteriorly pushed [19,20]. A similar metric, the center gravity of the head to C7 SVA (CGH-C7SVA), is also associated with increased risk of postoperative kyphotic failure following laminoplasty [20].…”
Section: Sagittal Parametersmentioning
confidence: 99%
“…Additionally, an elevated T1 slope and cSVA predict postoperative kyphotic deformity as the center of the head mass is anteriorly pushed [19,20]. A similar metric, the center gravity of the head to C7 SVA (CGH-C7SVA), is also associated with increased risk of postoperative kyphotic failure following laminoplasty [20]. Lastly, the occipital cervical angle (OCI) is a critical measurement in one's ability to maintain a normal gaze with increased OCI associated with the presence and progression of ASD [21].…”
Section: Sagittal Parametersmentioning
confidence: 99%
“…Laminoplasty is suggested as an alternative option because of its advantages in maintaining the motion of the cervical spine while maintaining the integrity of the posterior neck muscles and preventing epidural scar formation 26,32 . However, many reports have highlighted that laminoplasty can result in radiological kyphotic changes after surgery, although the risk is lower than that with laminoplasty alone 33,34 . The surgical technique allows wide exposure of the spinal canal, and it can easily be extended intraoperatively caudally, or rostrally.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 32 However, many reports have highlighted that laminoplasty can result in radiological kyphotic changes after surgery, although the risk is lower than that with laminoplasty alone. 33 , 34 The surgical technique allows wide exposure of the spinal canal, and it can easily be extended intraoperatively caudally, or rostrally. On the other hand, the disadvantages of this technique include possible extradural scar formation, loss of posterior spinal column integrity, and spinal instability and deformity.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical spine range of motion (ROM) refers to the change in cervical lordosis (CL) in flexion and extension compared with the neutral position. Recent studies have reported that preoperative cervical ROMs are important predictors for changes in cervical sagittal alignment (CSA) and clinical outcomes after cervical LMP [ 3 9 ]. Fujishiro et al [ 4 ] speculated that a large cervical flexion range of motion (Flex ROM) indicated that posterior neck muscular-ligament complex (PMLC) forces restricting motion toward the kyphotic position were weak, and Lee et al [ 5 ] thought that a small cervical extension range of motion (Ext ROM) indicated the low contraction reserve of PMLC.…”
Section: Introductionmentioning
confidence: 99%